Comparison of damping performance of an aluminum bridge via material damping, support damping and external damping methods. (November 2022) - He, Wei; He, Kewen; Yao, Cunxu; Liu, Peng; Zou, Chao
Highlights: Three measures via material damping, support damping and external damping methods to increase damping of an aluminum bridge are considered and compared. Proper damping mechanism of each method is discussed. Effect of structural strain and structural frequency on system damping is checked. External damper is found to be most effective in damping increment. Abstract: Damping property is the basic energy dissipation mechanism that widely exists in almost all kinds of structures or components. This paper presents an experimental study on three different measures including rubber sheet pavements, rubber bearings and external passive damper to increase the damping of a lightly damped aluminum bridge. These methods are conventional treatments in engineering practice, and they aim to take effect through the aspects of material damping, support damping and external damping, respectively. The performance of these methods in damping increment is compared, and the possible damping mechanism of each measure is discussed. The external damper is found to be most effective in damping increment, followed by rubber bearings. The method of rubber sheet pavement is inefficient in damping increment owing to the huge difference in elastic modulus between aluminium and rubber. The rubber sheet keeps in tiny strain state during structural vibration and fails to generate effective internal friction between particles, and thus contributes little to the overall material damping. This indicates that the damping material method can take effect only if the damping layer has not only remarkable loss factor but also comparable elastic modulus with the target structure. In addition, the external damper generally follows the linear viscous damping law. The external damper having liquid viscosity of 3.05 Pa·s can increase the system damping to 1.5 %, which is almost one order greater than the performance of rubber sheet pavement and rubber bearing methods. Moreover, the external damping method is found to be sensitive to the installation location of the damper. The greater the modal displacement, the larger the system damping is. Furthermore, the system damping is not sensitive to structural frequency, whereas it slightly increases with the structural strain in small strain levels.